2012
DOI: 10.1007/s00270-012-0399-8
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Lung Microwave Ablation in a Porcine Tumor Mimic Model

Abstract: A single microwave antenna can create ablation zones large enough to cover lung tumor mimic models of ≤4 cm with no heat sink effect from vessels of ≤6 mm. Synergic use of 3 antennas allows ablation of larger volumes than single-antenna or radiofrequency ablation, but great caution must be taken when 3 antennas are used simultaneously in the lung in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Compared to RFA, less research is available on MWA, but it is a promising option because it offers larger ablation zones, reduced procedure times, and decreased heat‐sink effects . In our study, we focused on a comparison of RFA and MWA for the treatment of lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to RFA, less research is available on MWA, but it is a promising option because it offers larger ablation zones, reduced procedure times, and decreased heat‐sink effects . In our study, we focused on a comparison of RFA and MWA for the treatment of lung tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This fact renders the heat produced by RFA vulnerable to being washed out by vessels as small as 3 mm, a phenomenon known as the heat sink effect [35,36]. In contrast, MWA, whose heating deposition ability is favored by the presence of water, has been proven to be less susceptible to the heat sink effect by inducing complete thrombosis of most vessels with a diameter < 6 mm [37,38].…”
Section: Advantages Of Microwave Ablationmentioning
confidence: 99%
“…The postprocedural evolution of the ablation zone is usually divided into three continuous phases with corresponding histologic and imaging findings [55 -57]. The features of the thermally ablated lung tissue have first been described after RFA, but are similar to those after MWA [37,38].…”
Section: Imaging Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper it was shown that MWA has less heat sink effect: in models a single MWA antenna can create ablation zones large enough to cover lung tumor of <4 cm diameter with no heat sink effect for vessels up to 6 mm (22). In clinical practice the advantage of the method MWA lies in faster reaching therapeutic temperatures, applicable higher temperatures, and faster ablation.…”
Section: Mwa Versus Rfamentioning
confidence: 99%